(3OjhGf GdJgGejs - (3Ydj Hf eMeO Hf agO, CHh GdMSf GdJgGej,J (B416 (3g` s
(3ChdgG (B:s
(3bGd jeOM GdTQja C(B[(3GYHOGddg GdMSjf Hf EHQGgje GdMSfj HGdQedI HYKJ Edjc HWjagG JYdjdkG hNVGH djdc bO CQGO fUhdG s
(3BNQgG (B:s
(3Cde NjGdgG HYO GdQLhY aYGOJ EP QCJ Sjaj fLjYj hgGLJ dj HRhQJgG RajQkG jcGO jbje eYhL GdVdhY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3ZjQ eQJH Ydi GdbhGaj Ch GdehVhYGJs
(3haj ChdgG Jedc SfI (B997 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B145 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B219s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B61 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B771s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs